Dermatofyta klinicky zdravých psů a kocek - Komárek, J; Wurst, Z (Veterinarni medicina, 1989)
The hair and skin of 300 clinically healthy animals, 268 dogs and 32 cats, were examined mycologically. The method described by Mariat and Tapia (1966) was used for the examination, along with square pieces of the fitted carpet Kovral. The dermatophytes were isolated in 12 samples, all from the material taken from dogs. Trichophyton mentagrophytes was isolated six times, Microsporum canis four times, Trichophyton gallinae once, Trichophyton rubrum once. The origin of the dermatophyte Trichophyton gallinae, found in a village dog, was not determined. In one case of occurrence of the dermatophyte Trichophyton mentagrophytes in a dog the dermatophyte was probably transmitted from man to the dog. Microsporum canis was not proved to be the most frequent dermatophyte in dogs or cats in this country.
Keywords: Dogs; Cats; zvířata; Arthrodermataceae; psi; kočky; Animals